Dynamic correlations between inhomogeneous magnetic fields, internal gradients, diffusion and transverse relaxation, as a probe for pore geometry and heterogeneity - Seland, John Georg (Diffusion Fundamentals, 2014)
In this study we have applied 2D NMR experiments where the spatial inhomogeneous magnetic field (Bi) inside a porous sample is correlated to respectively internal gradient (G0), diffusion coefficient (D), and transverse relaxation time (T2) of a confined liquid. Experiments were performed on samples having different pore system geometry and heterogeneity, leading to different types of confinement of the liquid. The results show that the correlation between G0 and Bi is more sensitive to the type of confinement, and thus also of the pore geometry and heterogeneity, compared to the corresponding correlations involving D and T2.